The impact of environmental tax policies on artificial intelligence investment: evidence from agri-food, food processing, and other industries - Guangxing Hu; Bin Li; Juhao Lai (Frontiers in Sustainable Food Systems)
This study investigates the impact of China's Environmental Protection Tax on corporate investment in artificial intelligence (AI), with a particular focus on listed firms in the agri-food and food processing industries. Using the 2018 implementation of the Environmental Protection Tax Law as a quasi-natural experiment, the analysis employs a difference-in-differences (DID) approach based on panel data from 2010 to 2022. The findings demonstrate that the tax reform significantly promotes AI investment, especially among state-owned enterprises, manufacturing firms, and those located in resource-based regions. The study further reveals that the mechanism underlying this effect lies in the alleviation of financing constraints and increased research and development input. These results highlight the important role of environmental regulation in driving digital transformation and green innovation, providing both empirical evidence and practical guidance for policymakers and industry stakeholders seeking to align environmental governance with technological progress.